Molecular characterization of Lipoptena cervi from environmental samples collected in Poland. (April 2021) - Gałęcki, Remigiusz; Jaroszewski, Jerzy; Bakuła, Tadeusz; Xuan, Xuenan
Abstract: The activity of Lipoptena cervi has intensified in Poland in recent years. The population genetics of this ectoparasite in Poland has never been described in the literature. The objectives of this study were to investigate the population genetics of L. cervi in selected regions of Poland, to evaluate molecular differences between L. cervi populations, and to determine phylogenetic relationships with other L. cervi sequences obtained in previous studies. In 2019, louse flies were sampled in natural mixed forests in five Polish voivodeships. Seven samples of L. cervi were collected from each voivodeship, and a total of 35 insects were analyzed molecularly. In the first step, Lipoptena spp. were identified to species level under a stereoscopic microscope. A fragment of the rRNA 16S gene was used as a marker to identify L. cervi by the PCR assay. The sequences were assigned accession numbers MT337409 to MT337416. A total of eight haplotypes were identified, two of which were dominant. In the obtained sequences, intraspecific pairwise genetic distances varied between 0.000 and 0.0496 ( m = 0.0135; SD = 0.0149; SE = 0.0006; V = 110.11). Mean interpopulation diversity was d = 0.0135 ( SE = 0.0027). The acquired nucleotide sequences were highly similar to the sequences from the Czech Republic (MF495940, AF322437), Lithuania (MN889542-MN889544) and Poland (MF541726–MF541729). The similarity with GenBank sequences ranged from 97.24% to 100%. This study revealed two dominant haplotypes of L. cervi in Poland, MT337410 and MT337413. Fragments of the analyzed sequences were detected in only one voivodeship. These findings suggest that the two dominant sequences are the oldest sequences that gave rise to the locally identified haplotypes. The lack of significant correlations with the sequences obtained in regions situated west of the research sites suggests the presence of other genetic populations in Europe. Graphical abstract: Image 1 Highlights: Eight new haplotypes with 0.000–0.0496 intraspecific pairwise genetic distance. Similarity with sequences from GenBank ranged from 97.24% to 100%. Two dominant haplotypes of L.cervi were observed in Central Europe. Part of the sequences have been discovered in single studied location. The lack of significant connections with sequences obtained from West Europe.